PH variation of MS medium for In vitro culture depending on agar concentration and initial pH - de Barros, Inacio; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 1992)
Murashige & Skoog (MS) medium was adjusted for different pHs (4.7, 5.7, 6.7 and 7.7) and supplemented with agar at several concentrations (0.0, 3.5, 7.0, 10.5 and 14.0 g/I). After dissolution of agar on hot plate at 50-55oC temperature the pH of media was measured. The medium was sterilized by autoclaving for 20 min at 120oC, and after, the pH was registred again. The pH after hot plate treatment increased in acid medium, it almost did not change in near neutral, and decreased in alkaline medium. The autoclaving acidified the medium particularly as higher was the initial pH. The agar showed a buffer effect on pH variation. During the autoclaving, the extremes of acidification took place in the medium without agar reducing 0,82 units in initial pH 7.7 and 0.18 units in initial pH 4.7. The higher alkalization (0.72 units) on hot plate treatment took place in the medium with 14.0 g/I agar and inicial pH 4.7.